An Overview of Tsunami Wave Force on Coastal Bridge and Open Challenges - Mazinani, I. (World Scientific, 2015)
Hundreds of bridges were washed away or heavily damaged by tsunami waves during the two tragic tsunamis that devastated the west coast of Sumatra Island, Indonesia, in 2004 and North East Japan in 2011. This vast damage was a clear warning for scientists to pay more attention and investigate, assess and mitigate the effect of tsunami loads on various structures including bridges. This multidisciplinary research presents a review of the literature and comprehensive evaluation on previous research concerning the effect of tsunamis on bridges. It begins with the basic evaluation of tsunami loads on bridges through to the current tsunamis. The experimental, numerical and survey reports on tsunami loads on bridges are reviewed and discussed. Tsunami mitigation systems on bridges are examined and classified in this paper. In addition, the open issues and challenges are outlined for future studies to help evaluate new research concerning the assessment, design and mitigation of tsunami loads on bridges. Â© 2015 World Scientific Publishing Company.